POTRET PEREMPUAN MINANGKABAU DALAM ERA GLOBALISASI; SEBUAH REFLEKSI - zaiyardam zaiyardam (Kafa`ah: Journal of Gender Studies, 2012)
In a global life today, the contradictions in life seems to be the law of nature. Life will continue to change, the changes that can form the remains such and the changes may also be permanent.The important fact is  when people get many blessings from God, and the grace that he or she used to get as asset to make changes. In the context of women, they who are lucky to do many actions toward people are not lucky, so it can  be a seed  for change. Every small shape, the seeds of change that take  place continuously, the power will be  toobstruct it. The effort to improve the quality of human life especially for women who are not fortunate to do with the plan. Copyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i2.62